Optimization of Pectinase Production from Silkworm Excrement Using Aspergillus niger - Fuzhi Lu; Caimei Tan; Huizhen Li; Feng Qian (Fermentation)
Silkworm excrement, a byproduct of the sericulture industry, is rich in organic compounds and presents a sustainable substrate for enzyme production. This study investigates the potential of silkworm excrement as a substrate for pectinase production using Aspergillus niger submerged fermentation. Single-factor experiments and a Box–Behnken Design (BBD) were employed to identify and optimize the key medium components and their interactions. Results indicated that the optimal concentrations for maximum pectinase activity were CaCl2 at 0.437 g/L, orange peel powder at 4.223 g/L, (NH4)2SO4 at 15.761 g/L, and bran at 33.590 g/L. The optimized conditions achieved a pectinase activity of 20.505 U/mL, validating the robustness of the RSM model. This approach not only maximizes enzyme activity but also presents a sustainable and cost-effective method for utilizing a byproduct in the sericulture industry, aligning with principles of circular economy and waste minimization.